Analisis Faktor yang Mempengaruhi Kecemasan Pasien Sebelum Anestesi - Ramadhanty, Andi Fitrah (Asosiasi Guru dan Dosen Seluruh Indonesia, 2025)
Background: Pre-anesthesia anxiety is a common phenomenon that can affect a patient's physiological and psychological state and impact the perioperative process. Identifying factors influencing patient anxiety is important for planning educational interventions and psychosocial support. Objective: This study aimed to analyze factors influencing patient anxiety before anesthesia, including demographic factors, previous experience, family support, and preoperative information. Methods: The study used a descriptive analytical design with a cross-sectional approach. The sample consisted of 100 elective patients undergoing general or regional anesthesia at Hospital X, selected using purposive sampling. The instruments used were a demographic questionnaire and the Hamilton Anxiety Rating Scale (HARS). Data were analyzed using the chi-square test and logistic regression. Results: The results showed that patient anxiety levels were associated with young age (p = 0.032), low education (p = 0.018), first-time surgical experience (p = 0.001), minimal family support (p = 0.005), and lack of preoperative information (p = 0.001). The dominant factor influencing anxiety was a lack of preoperative information, with an OR of 3.5. Conclusion: Patient anxiety levels before anesthesia are influenced by age, education, surgical experience, family support, and preoperative information. Preoperative educational interventions and family support are important strategies for reducing patient anxiety.